Assessment of Soil Pollution in the Ishaqi Project Area- Salah Al-Dean Governorate, Iraq - Al-Dabbas, Moutaz A.; Abdullah, Marwa A. (Iraqi Journal of Science, 2020)
Ten soil samples were collected from Ishaqi project area, Salah Al-Dean Governorate, and analysed for chemical elements (Fe2O3, Al2O3, CaO, K2O Na2O, Co, Zn, Cu, and Pb) to detect the pollution in the study soil using the indices of geo-accumulation (I-geo), contamination factor (CF), and pollution load index (PLI), The results of I-geo indicate that the soil of Ishaqi project area is unpolluted with Pb, Co and slightly polluted with Zn and Cu. The results of CF for Zn, Cu, and Co showed class 2 of moderate contamination and class 1 of low contamination in some samples while those for Pb demonstrated class 1 –of low contamination. The Pollution Load Index (PLI) values for Co, Zn, Cu, and Pb showed class 2 of local pollution.